2018
DOI: 10.15302/j-fase-2018235
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effects of grape seed polyphenolics to prevent metabolic diseases

Abstract: Obesity is increasing in developing countries. Population studies show a relationship between affluence and obesity. Changing food intake patterns with affluence such as preference for foods with less astringent polyphenolic compounds and dietary fibers may increase risk of metabolic dysfunctions due to caloric imbalance. Animal models of obesity consistently show that grape seed procyanidins prevent increases in body and abdominal adipose weight gain, plasma cholesterol, liver weight gain and inflammation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Chardonnay marc is composed mainly of grape skins, seeds, and stems that are separated from the grape juice during pressing. Initiatives to eliminate wasteful practices and, instead, utilize the whole plant have led to the discovery that marc contains a rich source of health-promoting molecules . Previous studies have shown that Chardonnay and other grape seed flours improve cardiovascular health, , gastrointestinal health via modulation of the microbiome, and modulation of inflammatory response, , suggesting that Chardonnay marc may also have the potential to benefit human well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Chardonnay marc is composed mainly of grape skins, seeds, and stems that are separated from the grape juice during pressing. Initiatives to eliminate wasteful practices and, instead, utilize the whole plant have led to the discovery that marc contains a rich source of health-promoting molecules . Previous studies have shown that Chardonnay and other grape seed flours improve cardiovascular health, , gastrointestinal health via modulation of the microbiome, and modulation of inflammatory response, , suggesting that Chardonnay marc may also have the potential to benefit human well-being.…”
Section: Introductionmentioning
confidence: 99%